Grape Leaf Disease Detection Using Convolutional Neural Network - Muhammad Faza Iqmal Mustafa Kamal; Aminurrashid Noordin; Madiha Zahari; Ruzairi Abdul Rahim; Mohd Ariffanan Mohd Basri; Izzudin Mat Lazim (Malaysian Society for Computed Tomography & Imaging Technology (MyCT), 2026)
Non-Indexed Publication